Thymic hyperplasia with lymphoepithelial sialadenitis (LESA)-like features: a case report and literature review - Wenfeng Xu; Long Wang; Hao Tang; Ling Luo; Yujuan Xu; Deyu Guo (BMC, 2023)
Abstract Background Thymic hyperplasia with lymphoepithelial sialadenitis-like features (LESA-like TH) is a rare form of thymic hyperplasia, characterized by a prominent expansion of the thymic medulla containing hyperplastic lymphoid follicles with germinal centers, while an almost total absence of thymic cortex. Since the first report in 2012, only a few cases of LESA-like TH have been reported in the literature to date. Due to the rarity of LESA-like TH and the tumor-like morphology, it is easy to be misdiagnosed as other common diseases of the thymus in routine practice, such as thymoma and lymphoma. Case presentation Herein, we present a case report of a 52-year-old Chinese female patient with LESA-like TH, without any discomforting symptoms. Computer-tomography imaging revealed a cystic solid mass in the anterior mediastinum, with well-defined boundaries and multiple internal septa. Histologically, prominent features were florid lymphoid follicles containing germinal centers, as well as hyperplasia of thymic epithelial cells and proliferation of Hassall bodies. However, the thymic cortex rich in immature T cells was almost completely absent. Furthermore, mature plasma cells, lymphoepithelial lesions, and cholesterol clefts were frequently seen. Conclusion We made a diagnosis of LESA-like TH and performed a literature review to better understand the clinicopathological features of LESA-like TH and reduce misdiagnosis.